Implementation of E-Government-Based Policies in Improving Public Service Satisfaction in the Majalengka Regency Local Government - Yeti Kuswati; Tati Hartati; Dody Kusmayadi (Universitas Pendidikan Ganesha, 2022)
The service condition in Indonesia is considered very bad because corruption, collusion, and nepotism are still found in public services. In addition, the government is still faced with several phenomena related to public service problems, including those related to services that are complicated, long, and require money, so this is what creates a negative image of the government. This study aims to analyze and examine the application of e-government-based services in increasing public service satisfaction. This research is included in quantitative research using descriptive and verification methods. Methods of data collection using observation, interviews, and questionnaires. The research population amounted to 395 respondents, and the number of samples was 126. The collection instrument with interview sheets and questionnaires. The data analysis technique used descriptive analysis and verification analysis. The study results are that e-government services have a high level of accuracy, effectiveness, and efficiency in providing services because e-government-based services are considered effective in minimizing the error rate in the service process. However, the achievement of e-government-based services in Majalengka Regency is still faced with various challenges, especially those related to the support of facilities and infrastructure, technology support and network stability, as well as the support of human resources as managers.